2007
DOI: 10.4049/jimmunol.179.11.7883
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl Leukotrienes Are Autocrine and Paracrine Regulators of Fibrocyte Function

Abstract: Pulmonary fibrosis is characterized by the accumulation of fibroblasts and myofibroblasts. These cells may accumulate from three potential sources: the expansion of resident lung fibroblasts, the process of epithelial-mesenchymal transition, or the recruitment and differentiation of circulating mesenchymal precursors known as fibrocytes. We have previously demonstrated that fibrocytes participate in lung fibrogenesis following administration of FITC to mice. We now demonstrate that leukotriene-deficient 5-LO−/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 40 publications
(54 reference statements)
4
58
1
Order By: Relevance
“…This is the first description of the ability of AECs to produce LTs. CysLT levels are elevated in patients with IPF (27), and LTdeficient mice are protected from experimental fibrosis (28,29). It is possible that the increased cysLT production in AECs induces the secretion of TGF-b1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first description of the ability of AECs to produce LTs. CysLT levels are elevated in patients with IPF (27), and LTdeficient mice are protected from experimental fibrosis (28,29). It is possible that the increased cysLT production in AECs induces the secretion of TGF-b1.…”
Section: Discussionmentioning
confidence: 99%
“…The production of cysLTs by latently infected AECs is likely to promote fibrosis via effects on mesenchymal cells. We have previously reported that cysLTs can cause fibrocytes to proliferate (29). Additionally, cysLTs are known to induce fibroblast proliferation (44) and collagen secretion (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They promote the proliferation of human bone marrowderived fibroblasts, which participate in tissue remodeling and repair 8) . Also human bronchial fibroblasts can produce both LT B4 and cysteinyl LTs 9) .…”
Section: Introductionmentioning
confidence: 99%
“…Medina et al demonstrated that LTD 4 and IL-1β could induce the secretion of MMP-1 in airway smooth muscle cells resulting in the stimulation of cell proliferation [30]. More recently, it has been suggested that LTD 4 has the potential to augment fibroblast chemotaxis, and to contribute to the regulation of the wound healing and remodeling in fibrotic processes of the lung [31,32]. LTD 4 may also increase collagen production in activated myofibroblasts by upregulating CysLT1 receptor induced by TGF-β 1 [33].…”
Section: Discussionmentioning
confidence: 99%